A comparative clinical study on Vyoshadi Guggulu andBilwadi Kwath in the management of Sthoulyawith special reference to physical parameters of Obesity - Mothaliya, Khyati; Dadhich, Omprakash; Chhimpa, Rakesh (International Research Journal of Ayurveda & Yoga, 2020)
Introduction-Obesity is a condition in which the body weight disproportionate to height of a person. And this is due to the deposition of fat over body. Worldwide prevalence of obesity has been got tripled by 1975 to 2016. Obesity can be correlated with Sthoulya as per Ayurvedic perspective. As obesity becomes as a threatening condition around worldwide, it is indeed to find out an effective Ayurvedic formulation to treat Sthoulya. Aims - The primary aim of this study was toassess and compare the effects of Vyoshadi Guggulu and Bilwadi Kwath inthe management of Sthoulya (Obesity) with the help of physical parameters. Materials and Method-30 obese patients were enrolled who were randomly divided into three groups, 10 obese patients in each group. In Group A,500mgVyoshadi Guggulu was given withluke warm water twice a day.In Group B 20ml Bilwadi Kwathwas givenwithmadhu twice a day and in Group C, Vyoshadi Guggulu (500 mg) twice a day with luke warm waterandBilwadi Kwath(20 ml) twice a day with madhuwas given. Intervention was continuedfor 45 days with all three groups. Total three visits were done at an interval of 15 days.Assessment was done for reduction in weight (Kg) and Body Mass Index (B.M.I.) of all the subjectswho hadparticipated in the study. Result-In weight, 5.86%relief was found in Group A; 2.54%relief was found in Group B whereas 7.55% relief was obtained in Group C. In BMI, 6.53% relief was found in Group A,3.70%relief was found in Group B while 8.45% relief was obtained in Group C. Conclusion-Thus it was concluded that administration of Vyoshadi Guggulu andBilwadi Kwathtogether(Group C)has shown better result in reduction of weight (Kg) and B.M.I than the interventions done in Group A and Group B respectively.